2015
DOI: 10.1515/fhort-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Plant thin cell layers: update and perspectives

Abstract: Thin cell layers (TCLs) are small and versatile explants for the in vitro culture of plants. At face value, their morphogenic productivity may appear to be less than conventional explants, but once the plant growth correction factor and geometric factor have been applied, the true (potential) productivity exceeds that of a conventional explant. It is for this reason that for almost 45 years, TCLs have been applied to the in vitro culture of almost 90 species or hybrids, mainly ornamentals and orchids, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
1
17
0
7
Order By: Relevance
“…It has been reported that light treatment delays callus formation from thin cell layers in apple cultivars [26,27]. However, the transverse thin cell layers of domestic apples used as explants under light showed higher shoot regeneration capacity than those under a dark treatment [28]. Additionally, adventitious shooting is species dependent [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that light treatment delays callus formation from thin cell layers in apple cultivars [26,27]. However, the transverse thin cell layers of domestic apples used as explants under light showed higher shoot regeneration capacity than those under a dark treatment [28]. Additionally, adventitious shooting is species dependent [29].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of these explants requires stability of hand and thus intensive labor is necessary that does not currently allow the technique to be mechanized, thereby restricting its use across a wide range of plant species (Teixeira da Silva and Tanaka, 2011). Despite this, TCLs have served as useful alternative explants for dozens of plant species, now exceeding 100 (Teixeira da Silva and Dobránszki, 2015). The TCL portfolio includes plant species for which well-established regeneration protocols exist such as the model plants tobacco (Nicotiana tabacum L.) and Arabidopsis thaliana (L.) Heynh.…”
Section: Tcls In In Vitro Organogenesis: History Successes Limitatimentioning
confidence: 99%
“…Thus, the ability to have a tissue culture system that can produce a larger number of clonal propagules, relative to conventional explants, makes TCLs attractive to researchers and the ornamental industry. To date, the TCL technology has been used in tissue culture or micropropagation of 19 orchid species spanning 13 genera where it has also been used for the induction of cultures leading to in vitro flowering (Teixeira da Silva, 2013; Teixeira da Silva et al, 2014; Teixeira da Silva and Dobránszki, 2015) or the induction of somatic embryos, which are equivalent to PLBs (Teixeira da Silva and Winarto, 2016). When used with juvenile tissues of conifer and forestry tree species that are usually difficult to micropropagate since mature tissues tend to be recalcitrant in vitro (Benson, 2000;Bonga, 2017), TCLs offer a viable opportunity for regeneration.…”
Section: Tcls In In Vitro Organogenesis: History Successes Limitatimentioning
confidence: 99%
See 2 more Smart Citations